2009
DOI: 10.1111/j.1467-9485.2009.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Pay Gap Under Duopsony: Joan Robinson Meets Harold Hotelling

Abstract: This paper presents an alternative explanation of the gender pay gap resting on a simple Hotelling‐style duopsony model of the labour market. Since there are only two employers, equally productive women and men have to commute and face travel cost to do so. We assume that some women have higher travel cost, e.g., due to more domestic responsibilities. Employers exploit that women on average are less inclined to commute and offer lower wages to all women. Since women's firm‐level labour supply is for this reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…One could argue that large metropolitan areas are trend‐setters with more progressive environments and less discriminatory employers leading to less Beckerian discrimination. This kind of reasoning, however, suffers from several shortcomings (for details, see Madden, ; and Hirsch, ). In particular, Beckerian discrimination is costly for employers and should therefore be competed away in the long‐run if labour markets are sufficiently competitive.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…One could argue that large metropolitan areas are trend‐setters with more progressive environments and less discriminatory employers leading to less Beckerian discrimination. This kind of reasoning, however, suffers from several shortcomings (for details, see Madden, ; and Hirsch, ). In particular, Beckerian discrimination is costly for employers and should therefore be competed away in the long‐run if labour markets are sufficiently competitive.…”
Section: Theorymentioning
confidence: 99%
“…What is needed for Robinsonian discrimination to work, however, is that labour markets are imperfectly competitive and that firms face more monopsony power over their female workers than over their male workers. Hirsch () presents a simple spatial duopsony model of the labour market in which workers are located at different places, while employers do not exist at each potential location. As a consequence, workers have to commute, facing some travel cost.…”
Section: Theorymentioning
confidence: 99%
“…The optimal wage of a rm i equals the weighted sum of the rm's net revenue product of labor, and the wages paid in neighboring rms, less a measure of the disutility cost t (as in To, 1999, 2003;Kaas, 2009;Hirsch, 2009). Own productivity, as captured by φ i (p i , r), has a positive wage eect because the gain in prots from increasing labor input becomes larger the more productive the additional worker is.…”
Section: Prot Maximizationmentioning
confidence: 99%
“…However, a number of recent theoretical papers argue that gender pay gaps can persist if markets are not perfectly competitive (e.g., Black 1995;Hirsch 2009;Lang and Lehmann 2012;Lang, Manove, and Dickens 2005;Rosén 1997;Rosén 2003;Sasaki 1999). For example, Black (1995) and Rosén (1997) develop equilibrium search models with prejudiced employers, who reduce outside options for all minority workers by influencing the number or quality of outside offers.…”
Section: Employer Discriminationmentioning
confidence: 99%
“…Although no study has shown whether firms adjust their pay-setting to their local discriminatory environment, a number of papers have provided evidence suggesting that gender pay gaps persist if firms have monopsony power and if search frictions are larger for women than for men (Bhaskar, Manning, and To 2002;Boal and Ransom 1997;Hirsch 2009;Hirsch et al 2010;Manning 2008;Robinson 1969). 3 Moreover, another related strand of the literature focuses on frictions in the product market to explain the persistence of discriminatory pay gaps.…”
mentioning
confidence: 99%